First record of Eurystyles actinosophila (Barb. Rodr.) Schltr. in the Central-West region of Brazil and notes on distribution of Eurystyles and Lankesterella (Orchidaceae, Spiranthinae) in Brazil - José Herlânio de Lima; Viviane Vaz Queiroz; Luciano de Bem Bianchetti (Check List, 2022)
We report the first record of Eurystyles actinosophila (Barb.Rodr.) Schltr. and the genus Eurystyles Wawra (Orchidaceae) in the Central-West region of Brazil. The species was found in the Brasília National Park, in Brasília, Distrito Federal, in the core region of the Cerrado. We also undertook a survey of collection sites in Brazil for species of Eurystyles and Lankesterella Ames, which together form the epiphytic clade of Spiranthinae, in order to create an updated distribution map. Previously identified only in the Atlantic Forest and Pampa, we note that some species of these two genera also occur in the Cerrado and Caatinga domains.